Usos da paisagem edênica no cinema brasileiro nos anos 1970: o caso de Como Era Gostoso Meu Francês - Macêdo, Gabriela Cavalcanti (2017)
This dissertation aims to analyze how the cultural memory of the perception of paradise and indigenous people were updated in the national cinematographic production throughout the Civil-Military Dictatorship (1964-1985), specifically in the film Como é gostoso meu francês by Nelson Pereira dos Santos. It is assumed that Paradise is a spatial conception historically constructed that, united with its main inhabitant (Native American) composes a spatial cut of the edenic landscape. The hypothesis is that Nelson Pereira dos Santos' film installed possibilities of allegorical readings through the use of this edenic landscape. The research relates the visual studies and the historical analysis, focusing in the identification of the visual and discursive matrices with which the film dialogues. However, for this it will be used the narrative-iconological methodology, based simultaneously on the narratology of David Bordwell (2013) and iconology of W.J.T. Mitchell (2000). For the former the narrative is fundamental for the understanding of the film’s object. As for the latter, the critical iconology of Mitchell (2000) allows access to the iconological elements and to the visibility regimes historically constituted. That said, the present dissertation will analyze the representations of the edenic landscape that lie in cultural and visual memory, which are present in the composition of the cinematographic image in a way that helps the understanding the manner the film perceives and constructs a certain image of Brazil.